Microbial ecology of selected traditional Ethiopian fermented products - Sanz-López, Carmen; Amato, Michela; Torrent, Daniel; Borrego, Marta; Anza, Mathewos; Bibiso, Mesfin; Grijalva-Vallejos, Nubia; Vilanova, Cristina; Porcar, Manuel; Pascual, Javier (Frontiers in Microbiology, 2025)
The consumption of traditional fermented foods and beverages plays an important role in the diet of Ethiopia, providing significant nutritional and health benefits to the local population. The present study aimed to investigate the microbial ecology and diversity of nine types of fermented products. These include two foods (Kotcho and Injera), one food condiment (Datta), and six beverages (Tej, Tella, Cheka, Kinito, Borde, and Shamita). A combination of metataxonomic and culturomic approaches was used to achieve a comprehensive characterization of the bacterial communities, together with a thorough physicochemical characterization of the fermented products. This study provides one of the most comprehensive microbial characterizations of a wide selection of Ethiopian fermented products, highlighting that some bacterial species involved in the fermentation processes could contribute to the safety and nutritional quality of fermented foods and, based on previous studies, could also play a key role in enhancing their potential probiotic properties.